If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 8y = -12 Solving -12x + 8y = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -12x + 8y + -8y = -12 + -8y Combine like terms: 8y + -8y = 0 -12x + 0 = -12 + -8y -12x = -12 + -8y Divide each side by '-12'. x = 1 + 0.6666666667y Simplifying x = 1 + 0.6666666667y
| -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 | | 3x-2=8x-1 | | 6.43-10d=2.5 | | -2c+5=-c+2 | | 9x+15=14x-11 | | 2a-17+20a-9= | | -2(2k-4)=4(k-2) | | 8-5(2-x)=5+3(x-4) | | 5x-1+7x=90 | | -2747=41k |